Peran Social Media Marketing, Brand Awareness, dan Harga Terhadap Keputusan Pembelian Mie Gacoan Pada Platform Marketplace GoFood - Alfizar, Agus Azmi; Nurhasanah, Saniatun (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research aims to analyze the influence of Social Media Marketing, Brand Awareness and Price variables on purchasing decisions for Gacoan Noodles on the GoFood marketplace platform. This research uses quantitative methods with the research object being Generation Z Mie Gacoan consumers in Jabodetabek. In this research, the Structural Equation Model (SEM) analysis technique was used with the Partial Least Square (PLS) method and the data was processed with the help of the SmartPLS 4 application. The results of this research stated that the role of Social Media Marketing, Brand Awareness, and Price had a positive and significant effect on Decision to Purchase Gacoan Noodles on the GoFood marketplace platform. There is an indirect influence between Social Media Marketing, Brand Awareness, and Purchasing Decisions which shows positive and significant results.